Pressure effect upon the dielectric response of KDP family crystals - Stasyuk, I.V.; Levitskii, R.R.; Moina, A.P. (Condensed Matter Physics, 1999)
Within the four-particle cluster approximation for the proton ordering model, we study the effects of external pressures (which do not lower the crystals' symmetry) upon static and dynamic dielectric properties of deuterated ferroelectrics and antiferroelectrics of KH₂PO₄ family. The theory provides a satisfactory description of the available experimental data. The importance of the pressure induced changes in the D-site distance in the dielectric response of the hydrogen bonded crystals is shown.